KESADARAN HUKUM MASYARAKAT BENGKALIS TERHADAP PELANGGARAN LALU LINTAS - MUHAMMAD ZAINAL; Erdianto Effendi; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Traffic and road transport in Indonesia has a very important and strategic role so that the organizers are controlled by the state, and its guidance is carried out with the aim of realizing the safe and smooth, safe, smooth and efficient traffic and road transport. In Indonesia the regulation on traffic and national road transport is regulated in Law of the Republic of Indonesia Number 22 Year 2009 on Traffic and Road Transportation. This law provides the basis and guidance on enforcement of traffic violations. The number of traffic violations in the Bengkalis District region from year to year is increasing, indicating the lack of public awareness in traffic order. The details of the number of violations obtained from the Police of the Republic of Indonesia Regional Riau Resort Traffic Unit Bengkalis Polres Year 2016 Violations 6,993, 2017 Violations 10,551.The type of research used by researchers is a type of sociological legal research, namely legal research conceptualized as a social institution that is in real terms associated with other social facts. The nature of this study is descriptive that is to provide accurate data about humans, legal factors, conditions or symptoms.From the research result Bengkalis community awareness level in the orderly traffic is still in the value of less and has not run optimally in accordance with the expected by traffic law. But the Bengkalis District Traffic Police has enforced the law against traffic violations, with repressive efforts that constitute activities covering two educative and juridical prosecutions. Educative act of repression in the form of reprimand and warning. While the jurisdiction is the action carried out by a ticket or a fine, legal awareness can be raised in several parameters, among others, in terms of the form of violation, the implementation of the law. Increased awareness of Bengkalis community law can basically be done through two ways, namely in the form of education. One of the efforts made is the direct socialization to the field, school, and directly to the village community. The result of the research shows that the causal factor of traffic violation by vehicle riders in Bengkalis City is caused by the man himself due to lack of awareness of traffic rules and other human interests, causing careless, negligent, even deliberate people to become the dominant factor of traffic violation in Bengkalis city.Keywords: Legal Awareness, Law Violations, Traffic